PspC, a Pneumococcal Surface Protein, Binds Human Factor H - Dave, Sandhya (American Society for Microbiology, 2001)
PspC was found to bind human complement factor H (FH) by Western blot analysis of D39 (pspC(+)) and an isogenic mutant TRE108 (pspC). We confirmed that PspA does not bind FH, while purified PspC binds FH very strongly. The binding of FH to exponentially growing pneumococci varied among different isolates when analyzed by fluorescence activated cell sorting analysis.